The lost world Jurassic Park - Molen, Gerald R.; Wilson, Colin; Koepp, David; Spielberg, Steven, 1946-; Goldblum, Jeff, 1952-; Moore, Julianne; Postlethwaite, Pete.; Howard, Arliss; Attenborough, Richard; Kaminski, Janusz, 1959-; Kahn, Michael, 1935-; Williams, John, 1932-; et al. (Universal City, CA : Universal Studios, 2000)
Four years after the disaster at Jurassic Park, dinosaurs have secretly survived on a nearby island and roam free. Now there is a more ominous threat--a plan to capture and bring the dinosaurs to the mainland. John Hammond sees a chance to redeem himself for his past mistakes and sends an expedition to reach the island before the mercenary team gets there. The two groups confront each other in the face of extreme danger and must team up for their own survival in a race against time.
DVD release of the 1997 motion picture.
Based on the novel by Michael Crichton.
Special features include: direct hotlink to the set of Jurassic Park III, "The making of The lost world," deleted scenes, storyboards, production photographs, design sketches, conceptual paintings, theatrical trailers, dinosaur encyclopedia, production notes, cast and filmmakers information.
Director of photography, Janusz Kaminski ; editor, Michael Kahn ; music, John Williams.
Jeff Goldblum, Julianne Moore, Pete Postlethwaite, Arliss Howard.
DVD ; Dolby surround.
Keywords: Crichton, Michael, -- 1942-2008 -- Film adaptations; Dinosaurs -- Drama; Feature films -- United States; Feature films; Science fiction films; Films for the hearing impaired